Computational fluid dynamics simulations of the flow field characteristics in a novel exhaust purification muffler of diesel engine. Issue 4 (December 2018) - Jun, Fu; ZengFeng, Zhang; Wei, Chen; Hong, Mao; JianXing, Li
The purpose of this paper is to improve the emission performance of diesel engines. A novel exhaust purification muffler was proposed and designed. The flow field characteristics of the exhaust purification muffler were studied based on the finite volume method, the pressure loss of the exhaust purification muffler was 3315 Pa, and the pressure loss of the exhaust purification muffler was just 2% higher than the original muffler. Then, a three-dimensional numerical simulation model was established and used to investigate the effect of different expansion ratio, cavity length ratio, and ratio of length to diameter on the flow field characteristics in an exhaust purification muffler of diesel engine. The study was shown that the porous media (ceramic foam) had a great influence on the flow field distribution, where the air flow velocity was stable and the pressure distribution was trapezoidal, having a good pressure reduction and deceleration effect. With the increase of the expansion ratio parameter, the airflow cross-section area changed when air entered into the inlet silencing cavity, which had great influence on the velocity field and the pressure loss. Because of the improvement of cavity length ratio parameter, the flowing distance in the inlet silencing increased, which caused more local turbulence and pressure fluctuation. Also with the increase of the ratio of length to diameter parameter, the volume of inlet silencing chamber and the air flow space increased. The change of the structural parameters of each scheme had a certain influence on the pressure loss. The maximum pressure loss changing value among the expansion ratio schemes was 878 Pa, then the maximum pressure loss changing value among the cavity length ratio schemes was 328 Pa, and it was 89 Pa among the cavity length ratio schemes. The pressure loss caused by the expansion ratio parameter changed greatly, and the pressure loss changing value caused by the change of the cavity length ratio parameter and the ratio of length to diameter parameter was relatively small. In this paper, a muffler which contained a ceramic foam and had the functions of exhaust soot purification and noise elimination was supplied. The effects of the structure factors on flow field characteristics were studied. The guidance for the design and improvement of muffler is able to be supplied in this paper.